Tooth Surface Design of Spiral Bevel Gear with Considering the System Meshing Misalignment Quantity - Qin Qiuxia Li Li Wang Yonghong Chen Haoyu (Jixie chuandong)
Based on the principle of tooth surface contact analysis considering system meshing misalignment quantity, taking the design of spiral bevel gears of an aeronautical reducer as an example, the calculation model of meshing misalignment quantity is analyzed and established. The meshing misalignment quantity of the system is calculated under the influence factors of manufacturing error, assembly error and loading deformation, and the design of tooth surface considering the meshing misalignment quantity is carried out. The tooth surface contact mark (TCA), loading mark (LTCA), transmission error, relative sliding speed of tooth surface, temperature rise of tooth surface and assembly mark and running-in mark in engineering application are obtained, and the processing parameters of gear pair are generated. The accuracy of the above design method is verified by the fatigue test of the actual gears, which provides a reference for the design, production and application of spiral bevel gears.